2014
DOI: 10.1038/mtm.2014.41
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of gene delivery strategies to efficiently overexpress functional HLA-G on human bone marrow stromal cells

Abstract: Mesenchymal stromal cells (MSC) constitutively express low levels of human leukocyte antigen-G (HLA-G), which has been shown to contribute to their immunomodulatory and anti-inflammatory properties. Here, we hypothesized that overexpression of HLA-G on bone marrow-derived MSC would improve their immunomodulatory function, thus increasing their therapeutic potential. Therefore, we investigated which gene transfer system is best suited for delivering this molecule while maintaining its immuno-modulatory effects.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 44 publications
2
16
1
Order By: Relevance
“…Furthermore, it is possible that the low expression of HLA-G1 contributed to allogenic NK cell proliferative response in semiallogenic fetus. On the other hand, HLA-G1 and HLA-G5 have an important role in the upregulation of T regulatory cells in the pregnant women [ 16 ]. Also, our results showed that the high expression of HLA-G resulted in an excess of IL-10 in the vaginal discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is possible that the low expression of HLA-G1 contributed to allogenic NK cell proliferative response in semiallogenic fetus. On the other hand, HLA-G1 and HLA-G5 have an important role in the upregulation of T regulatory cells in the pregnant women [ 16 ]. Also, our results showed that the high expression of HLA-G resulted in an excess of IL-10 in the vaginal discharge.…”
Section: Discussionmentioning
confidence: 99%
“…The vectors for gene delivery can be divided into two classes: viral and nonviral. Despite progresses in the development of nonviral gene delivery vector and transfection methods (e.g., in vivo electroporation, microporation, nanoparticles) to enhance the delivery efficiency, nonviral gene delivery is still generally considered less effective than viral vectors such as retrovirus/lentivirus, adenovirus, adeno‐associated virus (AAV) and baculovirus . In particular, transfection of adult MSCs is very inefficient …”
Section: Gene Therapy For Cartilage Engineeringmentioning
confidence: 99%
“…Boura et al () demonstrated that human bone marrow‐derived mesenchymal stem cells lentivirally engineered to overexpress HLA‐G1 decrease the proliferation of allogeneic T cells and their resistance against NK cell‐mediated lysis. In a similar study, pluripotent stem cells overexpressing HLA‐E were less detected by NK cells and allogeneic T cells (Gornalusse et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Especially, in xenotransplantation, where NK cells are critically important in foreign tissue rejection, HLA-G and HLA-E accompany with fair success. Also, the effect of soluble forms of these molecules on the tolerance in allotransplantation remains to be clarified in upcoming studies Boura et al (2014). demonstrated that human bone marrowderived mesenchymal stem cells lentivirally engineered to overexpress HLA-G1 decrease the proliferation of allogeneic T cells and their resistance against NK cell-mediated lysis.…”
mentioning
confidence: 99%